Design of non-linear filter in the problem of structural identification of biomedical signals with locally concentrated properties - Povoroznyuk, Anatoly; Filatova, A. E.; Myrgorod, Yuri (My University, 2013)
In this paper we propose a generalized method of structural identification of biomedical signals with locally concentrated properties using a digital non-linear filter. The experimental verification of the detecting function was performed by using different ways to describe the model of the desired class of structural elements.
Keywords: structural identification; biomedical signal; locally concentrated properties; digital non-linear filter; structural element